Merdeka Curriculum Implementation in TEFL At SMP IT Al Qudwah Musi Rawas - Windi Tri Apriyani; Maria Ramasari; Hamdan Hamdan (Edu-Ling: Journal of English Education and Linguistics, 2024)
The objectives of this research are to describe the implementation of Merdeka Curriculum and to identify English teachers' difficulties during the implementation of Merdeka Curriculum in TEFL at SMP IT Al Qudwah Musi Rawas. This research is descriptive qualitative. The sample of this research are English teachers at SMP IT Al Qudwah. The data were gathered by using observation checklist, interview, documentation and were analysed by Miles and Huberman Theory in the form of description. The findings showed that the English teachers made their own learning objectives and teaching modules based on the format from the government and then modified and adapted to the needs of students, Pembelajaran Terpadu and schools. Differentiated learning and Project Strengthening of Pancasila Students (P5) have been implemented by English teachers at SMP IT Al Qudwah. The difficulties faced by teachers were complicated administration, implementing differentiated learning, adjusting project hours to strengthen the Pancasila student profile, and having to prepare backup plans when using electronic media. To overcome these difficulties, the school provides extensive support to English teachers by involving teachers in learning committees, workshops, and inviting speakers from outside the school. In conclusion Merdeka curriculum has been implemented in TEFL at SMP IT Al Qudwah.